EVALUATION OF APPROPRIATENESS IN PRESCRIPTION OF GERIATRIC POPULATION IN RESIDENTS OF OLD AGE HOMES USING MAI CRITERIA - Salmanul Faris A; Satish S; A R Shabaraya (Journal of Biomedical and Pharmaceutical Research, 2020)
WHO evaluated that in every nine people there is one elderly individual, i.e. of age >60 years. Compared to young adults, elderly persons have more illnesses, as ageing is often accompanied by chronic diseases, co-morbidity, disability and social isolation. MAI was developed to evaluate appropriateness of medications in all age group. Objective of the study was to assess polypharmacy and appropriateness in prescription. A cross sectional study was carried out for a period of 6 months to assess medication appropriateness. Patients of both sexes above 60 years of age, with at least one chronic illness were included. Out of 481 drugs 32 drugs were marginally inappropriate and 53 drugs were inappropriate according to MAI criteria and 12 participants were completely frail according to GFI (GFI Score ≥4). Polypharmacy and PIM are highly prevalent in geriatric population, which has a major health care outcome. Standard criteria should be considered before prescribing the medications in geriatric population. Keywords: Geriatrics, polypharmacy, MAI.